2009
DOI: 10.1128/jcm.02216-08
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of the Recently Described Species Aeromonas aquariorum

Abstract: Twenty-two human extraintestinal isolates (11 from blood) and three isolates recovered from patients with diarrhea were genetically characterized as Aeromonas aquariorum, a novel species known only from ornamental fish. The isolates proved to bear a considerable number of virulence genes, and all were resistant to amoxicillin (amoxicilline), cephalothin (cefalotin), and cefoxitin. Biochemical differentiation from the most relevant clinical species is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 27 publications
7
64
6
Order By: Relevance
“…The expected genus-characteristic resistance against ampicillin was observed for our A. dhakensis strain. Also the results obtained for the susceptibility analysis of the rest of the antimicrobials tested agreed with those reported by other authors, showing that the cephalo sporins (third and fourth generation), monobactams, carbapenems, aminoglycosides, fluoroquinolones, sulphonamides, polypeptides and amphenicols tes ted were highly effective against this microorganism (Figueras et al 2009, Esteve et al 2012, Wu et al 2012, Chen et al 2013, Morinaga et al 2013.…”
Section: A Rivuli Cect 7518 T (Fj969433)supporting
confidence: 80%
See 2 more Smart Citations
“…The expected genus-characteristic resistance against ampicillin was observed for our A. dhakensis strain. Also the results obtained for the susceptibility analysis of the rest of the antimicrobials tested agreed with those reported by other authors, showing that the cephalo sporins (third and fourth generation), monobactams, carbapenems, aminoglycosides, fluoroquinolones, sulphonamides, polypeptides and amphenicols tes ted were highly effective against this microorganism (Figueras et al 2009, Esteve et al 2012, Wu et al 2012, Chen et al 2013, Morinaga et al 2013.…”
Section: A Rivuli Cect 7518 T (Fj969433)supporting
confidence: 80%
“…This bacterium was also occasionally isolated from stranded elephant seals, California sea lions and harbour seals (Thornton et al 1998). It is possible that the A. hydrophila identified phenotypically in those studies could belong, after a genetic identification, to A. dhakensis (synonym of A. aquariorum), as occurred in previous studies (Figueras et al 2009, Aravena-Román et al 2011, Morinaga et al 2013). In our case, pathologic and bac teriologic examination revealed an acute haemorrhagic-necrotizing pneumonia and sepsis associated with A. dhakensis, which was recovered in pure culture from lung, liver, spleen, kidney and blood.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The 2 A. dhakensis isolates shared an atypical pattern that is closely related to A. caviae. Figueras et al (2009) reported that A. dhakensis produce either the A. caviae RFLP pattern or a somewhat similar pattern with extra bands.…”
Section: Phylogenetic Analysis Using Rpod and Gyrbmentioning
confidence: 99%
“…Overall, 51 blood isolates were identified as A. aquariorum (16, 31 %), A. caviae (15, 29 %), A. veronii (12, 24 %), A. hydrophila (5, 10 %) and Aeromonas species (3, 4 %). Some of the isolates had been described previously (Wu et al, 2007;Figueras et al, 2009). The GenBank accession numbers for the rpoB gene sequences of A. aquariorum MDC47 T and 11 published A. aquariorum blood isolates are JF972604-JF972615.…”
Section: Species and Cpha-related Genes Distributionmentioning
confidence: 99%